On marine wind power expressiveness: Not just an issue of visual impact - Paolinelli, Gabriele; Fortuna, Lorenza; Marinaro, Ludovica; Valentini, Antonella (Frontiers in Energy Research, 2022)
Technological research for the exploitation of marine energy has produced significant advances which promise to expedite the process of transitioning to renewable resources. However, many issues hinder the effective exploitation of marine energy: among these are cultural concerns regarding the visual impacts of these technologies used. Assuming that “protecting” means preserving without banning evolutive changes, seascape protection and ecological transition are not alternatives because both converge toward sustainability. Even so, scientific concepts, technical practices, social perceptions, and the decisions and actions associated with them raise contradictions and conflicts. Within the complex challenge of ecological transition, clean energy availability arises as a necessary and imperative condition. This article proposes a critical landscape design perspective which focuses on the importance of understanding and expressing contemporaneity through the changes it brings to habitats and life. A focus on the visual impact of marine wind turbine is proposed as an example for a general discussion on technical and social perceptions in a context of both cultural and spatial transition. Site-specific critical visions have to be imagined and discussed to produce not business as usual transformations. This article aims to show that decisions predominantly influenced by issues of visual impact do not adequately express the cultural dimension of ecological transition.